Does the breast reconstruction method have an impact on time delay to adjuvant chemotherapy – A comparison between autologous and expander/implant breast reconstruction. (September 2022) - Lanthaler, Monika; Spechtler, Katharina; Krapf, Johanna; Egle, Daniel; Sieb, Michael; Tasch, Christoph; Spinelli, Rossella; Pierer, Gerhard; Bauer, Thomas
Summary: Introduction: This study aims to analyze whether autologous breast reconstruction as compared to expander/implant reconstruction has a higher risk of postoperative wound healing problems (WHPs) and thus potentially delays chemotherapy start. Methods: Between January 2012 and December 2019, a total of 64 women with NSME/SSME and autologous (Group1, n  = 33) or expander/implant reconstruction (Group2, n  = 31) and adjuvant chemotherapy were enrolled in this study conducted at Innsbruck Medical University Hospital. Immediate postoperative WHPs in each group were compared, and the time from operation to initiation of chemotherapy was analyzed. If the start of chemotherapy was postponed for more than six weeks postoperatively due to WHP, it was defined as delayed. Statistical analysis was performed with SPSS and Fisher's exact test. Results: More postoperative WHP occurred in Group 1 than in Group 2 (51.6% vs. 9.7%, p  < 0.001). Due to WHP, chemotherapy start was delayed for more than six weeks postoperatively in 30.3% of Group 1 patients and 3.2% of Group 2 patients. Only small differences in age (Group 1: 47±1 vs. Group 2: 46±2 years) and BMI (Group 1: 24.3 ± 0.6 vs. Group 2: 23.3 ± 0.7 kg/m 2 ) were found. Conclusion: Our study shows a far smaller risk for postoperative WHP and delay of chemotherapy start in the expander/implant group in comparison with the autologous group. In some selected patients with high urgency for adjuvant chemotherapy, a bridging operation by means of expander reconstruction prior to chemotherapy could be an oncologically safe pathway.